1995
DOI: 10.1242/jcs.108.4.1455
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of amino acid sequences in connexin43 involved in intercellular communication through gap junctions

Abstract: Gap junctions allow direct communication between cells without recourse to the extracellular space and have been widely implicated as important mediators of cell-cell signalling. They are constructed from the connexin proteins, which form a large family, and individual connexins show complex spatial and temporal variations in their expression patterns. Understanding how this variation contributes to the control of intercellular signalling, both in the adult and during embryonic development, is an important pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The amino acid sequences of Cx43 ELs have been frequently used as templates for the design of mimetic peptide blockers. Significantly, 43Gap26 (VCYDKSFPISHVR) and 43Gap27 (SRPTEKTIFII) are among the first peptide mimetics of Cx43 ELs [ 32 , 33 ]. These peptides were initially shown to inhibit gap junctional intercellular communication (GJIC) by reducing gap junction formation presumptively through their complementary interaction with the ELs, thereby preventing the docking of opposing Cx43HC [ 4 , 12 , 16 , 32 , 33 ].…”
Section: Selective Manipulation Of Cxhcmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid sequences of Cx43 ELs have been frequently used as templates for the design of mimetic peptide blockers. Significantly, 43Gap26 (VCYDKSFPISHVR) and 43Gap27 (SRPTEKTIFII) are among the first peptide mimetics of Cx43 ELs [ 32 , 33 ]. These peptides were initially shown to inhibit gap junctional intercellular communication (GJIC) by reducing gap junction formation presumptively through their complementary interaction with the ELs, thereby preventing the docking of opposing Cx43HC [ 4 , 12 , 16 , 32 , 33 ].…”
Section: Selective Manipulation Of Cxhcmentioning
confidence: 99%
“…Significantly, 43Gap26 (VCYDKSFPISHVR) and 43Gap27 (SRPTEKTIFII) are among the first peptide mimetics of Cx43 ELs [ 32 , 33 ]. These peptides were initially shown to inhibit gap junctional intercellular communication (GJIC) by reducing gap junction formation presumptively through their complementary interaction with the ELs, thereby preventing the docking of opposing Cx43HC [ 4 , 12 , 16 , 32 , 33 ]. The blocking effects of 43Gap26 and 43Gap27 on Cx43HC have been tested in a broad variety of cells and were shown to occur within minutes after administration, suggesting that existing CxHC are indeed targeted by these peptide blockers [ 34 , 35 ].…”
Section: Selective Manipulation Of Cxhcmentioning
confidence: 99%
“…Connexin-mimetics initially were synthesized for use as epitopes for connexin antibody production [130,131]. The blocking antibodies raised using these peptides against the EL and IL domains of several connexins were tested as GJ blockers and demonstrated some effect in reducing dye transfer in chick embryos [116]. However, EL loop antibodies Gap7M (EL1/2), Gap11 (EL1/2 Cx32), Gap15 (IL of Cx43), and Gap17 (CT Cx40) were found to be ineffective in functional testing and were not able to reduce connexin-associated contractile responses in rabbit arterial tone [92].…”
Section: Connexin-mimetic Peptidesmentioning
confidence: 99%
“…Despite this, Dahl et al described that peptides, used to generate antibodies, were effective in reducing Cx32 GJ formation and signaling in oocytes [132]. In 1995, Becker et al found that connexin-mimetic peptides, mimicking the sequences of the IL domain, could effectively block GJ channels when directly injected into embryo cells [116]. In the subsequent decades, a number of connexin-mimetic peptides have been generated and tested with a multitude of proposed functions including blockade of hemichannel and GJ signaling, alterations in GJ formation, and disruption of protein localization and protein-protein interactions (Table 1).…”
Section: Connexin-mimetic Peptidesmentioning
confidence: 99%
See 1 more Smart Citation